“We Take Hold of the White Man’s Worship with One Hand, but with the Other Hand We Hold Fast Our Fathers’ Worship”: The Beginning of Indigenous Methodist Christianity and Its Expression in the Christian Guardian , Upper Canada circa 1829 - David Andrew Kim-Cragg (Religions, 2023)
With more and more evidence coming to light of the cultural genocide inflicted by settler Christians upon Indigenous peoples through the residential school system, it is hard to see how Christian and Indigenous identities can hold together in the current Canadian context. Nevertheless, many in the Indigenous community within Canada continue to call themselves Christian, and Indigenous Christians continue to provide important leadership for the Canadian church. This phenomenon cannot be properly understood or appreciated without knowledge of the longstanding tradition of Indigenous Christianity and its origins. Beginning in 1829, Indigenous leadership within the Methodist Episcopal church in Upper Canada used the Christian Guardian to tell the story of their work among Indigenous communities. These Indigenous accounts of mission work provide a window into how early Indigenous converts to Methodism understood their faith and its meaning within the context of Canadian colonial Christianity, an understanding that differed in significant ways from that of their settler co-religionists. The early Indigenous narrative found in the settler Methodist publication emphasized Indigenous leadership, Indigenous language and the compatibility of Indigenous and Christian spiritual teachings. This study provides an important perspective which confirms and challenges contemporary views on Indigenous Christianity in Canada and helps to reimagine the past, present and future of Christianity in postcolonial contexts.